The Rise of China's Global Middle Class in International Perspective - Terry Sicular; Xiuna Yang; Björn Anders Gustafsson (Institute of Labor Economics (IZA), 2021)
Defining the 'global middle class' as being neither poor nor rich in the developed world, we estimate the size of the global middle class in China and 33 other countries and analyze China's expanding middle class in international perspective. China's global middle class has grown rapidly and has been catching up with that in developed countries. By 2018 China's global middle class constituted 25 percent of China's population; in absolute size it was nearly double the size of the global middle class in the US and similar in size to that in Europe. Cross-country analysis of the relationship between the middle-class population share versus GDP per capita reveals an inverted-U pattern. China is not an outlier from the cross-country pattern, but the speed with which its middle-class has expanded is unusual. The only other countries with similarly large, rapid expansions of the middle class are transition economies.
Keywords: D31; O53; P3; 330; China; middle class; income distribution; transition